2016
DOI: 10.4236/ojap.2016.52004
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the impact of air pollution on rates of hospitalization for asthma in Shiraz based on air pollution indices in 2007-2012

Abstract: Objectives: This study was designed to determine the effects of air pollutants on emergency admissions for asthma, and to forecast the disease burden in Shiraz, Iran. Methods: The average daily concentrations of fine particles (PM 10), nitrogen dioxide (NO 2), sulfur dioxide (SO 2), carbon monoxide (CO) and ozone (O 3) were calculated from data reported by two air quality monitoring stations in Shiraz from the beginning of 2007 to mid-2012. Results: The numbers of patients admitted with asthma attack during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
4
3
0
Order By: Relevance
“…According to our results, a 2-day lag exposure to SO 2 was associated with asthma exacerbation (OR = 1.97; 95% CI: 1.02-3.80), which is in accordance with previous studies on adults and children [24,27,30,31,39], while other authors have failed to observe such associations [25,33]. Gharehchahi et al [40] found a positive relationship between concentration of SO 2 and hospital admissions due to respiratory diseases in the elderly, while Galán et al [29] did not find any relationship between SO 2 and asthma emergency room admissions.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…According to our results, a 2-day lag exposure to SO 2 was associated with asthma exacerbation (OR = 1.97; 95% CI: 1.02-3.80), which is in accordance with previous studies on adults and children [24,27,30,31,39], while other authors have failed to observe such associations [25,33]. Gharehchahi et al [40] found a positive relationship between concentration of SO 2 and hospital admissions due to respiratory diseases in the elderly, while Galán et al [29] did not find any relationship between SO 2 and asthma emergency room admissions.…”
Section: Discussionsupporting
confidence: 93%
“…According to our results, a 2-day lag exposure to SO 2 was associated with asthma exacerbation (OR = 1.97; 95% CI: 1.02–3.80), which is in accordance with previous studies on adults and children [ 24 , 27 , 30 , 31 , 39 ], while other authors have failed to observe such associations [ 25 , 33 ]. Gharehchahi et al .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations